Political paradigms and communication science in political communication a review - Judijanto, Loso (Institute Of computer Science (IOCS), 2024)
This article articulates a review of the foundational concepts and evolving paradigms within the field of political communications, emphasizing the integration of communication sciences. Utilizing a qualitative approach through a literature review technique, the study explores the intersection of political paradigms and communication theories, offering insights into how these disciplines have shaped contemporary political communication practices. The review begins by outlining the basic concepts of political communications, tracing its historical development and highlighting key theoretical frameworks that have influenced its evolution. It then delves into various political paradigms, examining how these ideological frameworks impact communication strategies and public discourse. The article further investigates the role of communication sciences in enhancing the effectiveness of political communications, discussing the integration of media studies, rhetoric, and information theory. By synthesizing existing literature, the study identifies gaps in the current understanding and recommends areas for research in the future. This review contributes to the academic discourse by providing a nuanced understanding of how political and communication sciences paradigms converge to influence political messaging and public engagement. The findings underscore the importance of interdisciplinary approaches in advancing the study of political communications, offering valuable perspectives for scholars and practitioners alike